(untitled) (Journal of Rangpur Medical College, 2024)
Background: There is increasing evidence of a relationship between vitamin D status and type 2 diabetes. Diabetes has also been found to be associated with 25(OH)D (vitamin D) deficiency and the role of vitamin D has recently emerged, especially in preventing cardiovascular diseases and cancer. and insulin resistance. Objective: This study aimed to compare vitamin D deficiency between healthy and Type 2 Diabetes Mellitus (T2DM) patients. Methods: This cross-sectional study was conducted from July 2021 to June 2022 in the Department of Physiology, Rangpur Medical College, Rangpur. For this study, a total number of 100 subjects were selected among them 50 non-diabetic healthy subjects were included as control and 50 Type 2 Diabetes Mellitus patients were included as cases. The subjects of control were selected from the surrounding community of Rangpur district and subjects of cases were selected from Diabetic Association and from Outdoor of Endocrinology Department, Rangpur Medical College and Hospital, Rangpur. For statistical analysis, an independent sample t-test was performed by computer-based software SPSS-23.0 version for windows. Results: The mean vitamin D level was lower in the diabetic patients than in non-diabetic participants (14.1±8.3 ng/ml and 37.3±11.3, p<0.001). Conclusions: Early screening for serum vitamin D level is recommended for T2DM patients. Hence, it is crucial to promptly address any deficiencies in vitamin D levels. J Rang Med Col. March 2024; Vol. 9, No. 1: 77-81